Collaboration, editing, transparency: challenges and possibilities of a “wikification” of journalism - d'Andréa, Carlos (Brazilian journalism research, 2009)
This article discusses the possibilities and challenges of the incorporation of wikis in journalistic editorial offices, especially in the processes involving the drafting and editing of texts. The reflection takes into consideration a context marked by 1) continuous fragmented publication of information; 2) simplification and horizontal organization of journalistic routines, which directly impacts the figure of the editor (mainly in the media on the web); and 3) increasing public participation in the development of the news, with the mediation of professionals. “Wiki-journalism” practices on the Wikinews and Wikipedia sites and initiatives originating with print publications are presented and discussed, and based on them we distinguish two models, which differ in the degree of control of the process by the journalists.